Educating for sustainability: environmental pledges as part of tertiary pedagogical practice in science teacher education. Issue 3 (27th May 2017) - Paige, Kathryn
ABSTRACT: Educating for sustainability has been a key principle underpinning the primary/middle undergraduate teacher education programme at an Australian University for the past decade. Educating for sustainability seeks to provide knowledge and understanding of the physical, biological, and human world, and involves students making decisions about a range of ethical, social, environmental and economic issues, and acting upon them. This study (a part of the ongoing evaluation of our courses) focuses on pre-service teachers (PSTs) who have selected a minor in science and mathematics. Participatory and inclusive learning processes, transdisciplinary collaborations, experiential learning, and the use of local environment and community as learning resources as outlined by Sterling (2001) have formed the basis of much of our practice to develop PSTs' confidence and competence to teach science. This paper explores one pedagogical practice, environmental pledges which the preservice teachers undertook for 15 weeks. The focus is on the impact that undertaking an environmental pledge has had on the personal and professional lives of two groups, first, four cohorts of final-year science and mathematics pathway PSTs, and second, a small group of early-career teachers who had completed the course in previous years. Data have been collected from final-year science and mathematics students and early-career teachers using ethnographic methods to provide insight into their experiences of using the pledge.